(untitled) (Fiep Bulletin - online, 2014)
This cross-sectional study aimed to evaluate the nutritional intake, body image, risk of eating disorders and intention of behavior change of female brazilian athletes. sixty-nine athletes from different sports (teAm: volleyball, handball, indoor soccer and basketball n=46; com: judo, karate n=9; rG: rhythm gymnast n=14) had their anthropometric and body composition evaluated, answered questions on nutritional knowledge and beliefs, body image, eating disorders, and intention of changing eating behavior, and reported their 24h food intake. Athletes presented signifi cant difference in age (teAm: 17.3y±1.46; com: 20.6y±5.66; Gr: 16.0y±4.64; p=0.03). mean body mass index (bmi 19.91kg/m2±2.88) and fat percentage (%f 18.8±3.82) of rG were lower than teAm (23.26±2.65kg/m2, p=0.01; %f=23.98±5.31, p=0.03) and com (22.96±2.75kg/m2, p=0.021; %G=25.03±3.88, p=0.015). rG had de lowest mean energy intake (1533kcal±533). no differences in macronutrient intake were observed between groups. mean carbohydrate intake was low (<5g/kg/day) for all groups. Protein intake was high for 44.5% and 35.7% of com and rG, respectively. most athletes presented beliefs related to protein overvaluation. mean knowledge score was of 57% correct answers, with no difference between groups (p=0.775). knowledge did not correlate with the stage of intention of behavior change, for which athletes were evenly classifi ed in “preparation” (21.7%), “action” (18.8%) and “contemplation” (17.4%) stages. body image dissatisfaction and distortion were observed in 82.6% and 33.3%, respectively. of the 23 athletes with body distortion, 5 (21) % presented risk for eating disorder. the differences observed between groups allow us to design nutrition education strategies according to specifi c characteristics of sports.